Productivity of Boat Charts Operating in the Waters of Kao Bay, North Halmahera - Muhammad, Sofyan; Kadir, Irwan Abdul; Taeran, Imran; A. Harahap, Zulhan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The two-boat bagan is one of the most common fishing gear used by fishers in Kao Bay. Its main fishing target is squid with various other types of fish as by-products. Two-boat bagan operations are carried out every night so it is necessary to ensure the best moon phase for more efficient and effective catch. The purpose of the study was to analyze the composition of catch and to analyze the productivity of fish species and the moon phase. The data collection method was conducted by interview and observation of fishing operations for one month. Data analysis was carried out descriptively, using the composition formula and productivity analysis. The results showed that there were 7 types of fish caught by two-boat bagan. Three most dominant species were fish with high economic value, each with their respective compositions were squid (41%), selar (30%), and mackerel (17%). The types of catch with the highest productivity were squid (111 kg/trip), followed by selar (86 kg/trip), and mackerel (64 kg/trip). Based on moon phase, the highest fishing productivity took place in moon-phase 3 (931 kg/trip), followed by phase 2 (718 kg/trip), phase 4 (685 kg/trip), and phase 1 (534 kg/trip).